Balanced approach as an important factor of criminalization and decriminalization - Радутний, О. Е. (Theory and practice of jurisprudence, 2016)
The problem of criminalization and decriminalization of criminal acts considered from the perspective of a balanced approach, under which the author understands this attitude to new forms of illegal behavior, characterized by careful analysis, classification, identification of common features, removing pettiness description, comparison with the existing features of criminal law etc. As an example, consider the qualifying features that characterize the new forms and methods of committing crimes.